2020
DOI: 10.1101/2020.11.11.378323
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

N-Terminus ofDrosophila MelanogasterMSL1 Is Critical for Dosage Compensation

Abstract: The male-specific lethal dosage compensation complex (MSL complex or DCC), which consists of five proteins and two non-coding roX RNAs, is necessary for the transcriptional enhancement of X-linked genes to compensate for the sex chromosome monosomy in Drosophila XY males, compared with XX females. MSL2 is a single protein component of the DCC that is expressed only in males and is essential for the specific recruitment of the DCC to the high-affinity “entry” sites (HASs) on the X chromosome. MSL2, together wit… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 123 publications
(390 reference statements)
0
1
0
Order By: Relevance
“…Interaction of the CLAMP N-terminal zinc-finger with MSL2 is highly specific: in Y2H screening, we revealed that MSL2 only interacted with CLAMP and not with any other protein of the tested 152 multizinc-finger Drosophila transcription factors (14). Here we examined the structural basis for the interaction between the CLAMP and MSL2 proteins using NMR techniques and mutagenic screening complemented with in vivo experiments.…”
Section: Introductionmentioning
confidence: 99%
“…Interaction of the CLAMP N-terminal zinc-finger with MSL2 is highly specific: in Y2H screening, we revealed that MSL2 only interacted with CLAMP and not with any other protein of the tested 152 multizinc-finger Drosophila transcription factors (14). Here we examined the structural basis for the interaction between the CLAMP and MSL2 proteins using NMR techniques and mutagenic screening complemented with in vivo experiments.…”
Section: Introductionmentioning
confidence: 99%